Specific creatine rise in learned helplessness induced by electroconvulsive shock treatment - Sartorius, Alexander; Vollmayr, Barbara; Neumann-Haefelin, Claudia; Ende, Gabriele; Hoehn, Mathias; Henn, Fritz A. (Neuroreport, 2003)
Metabolic changes in the hippocampus formation can be investigated with in vivo magnetic resonance spectroscopy (MRS). Learned helplessness (LH) is a well validated animal model of depression which we established in Sprague-Dawley rats defining some as “learned helpless” (LH) or not “learned helpless” (NLH). Helpless and non-helpless rats received a course of daily administered electroconvulsive shocks (ECS) for 6 days. MRS measurements were performed on a 4.7 T animal scanner with an average voxel size within the rat hippocampus of 10 μl. In LH rats hippocampal creatine/NAA rose significantly (14%) whereas creatine/NAA of NLH rats showed no increase at all. A possible connection between hippocampal creatine levels and major depressive disorders as a reflection of changes in energy metabolism is discussed.
Gesehen am 03.11.2020